PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN PENALARAN DAN PRESTASI BELAJAR - Sari Aryani; Alexon (DIADIK, 2024)
This study aims to describe the application of discovery learning learning models to improve students' reasoning and achievement in Economics class X SMA Negeri 3 Muara Enim. The research design used is classroom action research and quasi-experimental research. The research subjects were students of class X IPS A at SMA Negeri 3 Muara Enim in Odd semesters for the academic year 2022/2023. Through simple random sampling technique, a quasi-experimental sample was obtained, namely class X IPA A for control class X IPA B at SMA Negeri 3 Muara Enim. The instrument of this study used observation sheets and tests. The research data were analyzed by descriptive statistics, average (mean), percentage, and t-test. The results showed that the application of the Discovery learning learning model could improve the reasoning and learning achievement of class X students of SMA Negeri 3 Muara Enim